2007
DOI: 10.1093/jxb/erm216
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of EIN3 homologues in basic PR gene expression and flower development in tobacco plants

Abstract: The TEIL (Tobacco EIN3-Like) gene is a tobacco homologue of arabidopsis Ethylene Insensitive 3 (EIN3), and the gene product binds an 8 bp sequence in the tobacco PR1a promoter in a sequence specific manner. It was found here that accumulation of TEIL transcript was induced by wounding and preceded basic PR gene expression. To study the downstream signalling pathway of TEIL, TEIL was overexpressed under the control of the constitutive 35S promoter in tobacco plants. In 35S::TEIL lines, basic PR genes, which are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 27 publications
1
21
0
Order By: Relevance
“…The TEIL (for Tobacco EIN3-Like) gene is a tobacco homolog of Arabidopsis Ethylene Insensitive3 (EIN3), a protein encoding a key transcriptional factor in ethylene signaling. Overexpression of both genes in the respective species was associated with protruded pistils (Guo and Ecker, 2003;Hibi et al, 2007) similar to the flower phenotype found in NappHS-silenced N. attenuata plants. Interestingly, flowers silenced in TEIL also exhibit pistil protrusion, demonstrating that the underlying mechanisms may be complex and related to differential perception of ethylene rather than increased or reduced sensitivity to this hormone.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…The TEIL (for Tobacco EIN3-Like) gene is a tobacco homolog of Arabidopsis Ethylene Insensitive3 (EIN3), a protein encoding a key transcriptional factor in ethylene signaling. Overexpression of both genes in the respective species was associated with protruded pistils (Guo and Ecker, 2003;Hibi et al, 2007) similar to the flower phenotype found in NappHS-silenced N. attenuata plants. Interestingly, flowers silenced in TEIL also exhibit pistil protrusion, demonstrating that the underlying mechanisms may be complex and related to differential perception of ethylene rather than increased or reduced sensitivity to this hormone.…”
Section: Discussionsupporting
confidence: 60%
“…The role of ethylene in pistil growth regulation was recently highlighted by Hibi et al (2007). The TEIL (for Tobacco EIN3-Like) gene is a tobacco homolog of Arabidopsis Ethylene Insensitive3 (EIN3), a protein encoding a key transcriptional factor in ethylene signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Ethylene appears to modulate EIN3/EIL at the protein level; treatment with 1-aminocyclopropane-1-carboxylic acid (ACC) results in the accumulation of EIN3 protein in Arabidopsis . Recently, tobacco TEIL has been found to have some relationship with the basic PR gene, as basic PR5 was induced in TEILoverexpressed plants; TEIL is also involved in flower development (Hibi et al, 2007). An important role for ethylene is in fruit ripening, and EIL genes have been isolated from fruit such as tomato (Solanum lycopersicum; Tieman et al, 2001;Yokotani et al, 2003) and kiwifruit (Actinidia deliciosa; Yin et al, 2008Yin et al, , 2009).…”
Section: Ecbs]) Was Also Found For Tobacco (Nicotiana Benthamiana) Tementioning
confidence: 99%
“…However, the EIN3/EIL gene family is considered to have a role in transcriptional regulation of target genes, such as Arabidopsis ERF1 (Solano et al, 1998) and tobacco basic PR (Hibi et al, 2007). In order to explore the relation between AdEIL genes and kiwifruit ripeningrelated genes, six such genes were selected for promoter isolation: AdACO1 (ACC oxidase, similar to the gene used in the ACO knockout kiwifruit; Xu et al, 1998), AdXET5 (xyloglucan endotransglycosolase; Schrö der et al, 1998;Atkinson et al, 2009), AdEXP1 (Yang et al, 2007), AdPG (the promoter of AdPG was confirmed in tomato; Atkinson and Gardner, 1993), and AdERS1b and AdETR1 (ethylene receptor genes; Yin et al, 2008).…”
Section: Adeil2 and Adeil3 Act As Transcriptional Activators By Intermentioning
confidence: 99%
“…The previous studies indicate that EIN3/EIL proteins can affect the "triple response" of seedlings (Chao et al, 1997), leaf, and root growth (Chao et al, 1997;Lee and Kim, 2003), female flower development (Chao et al, 1997;Hibi et al, 2007), and fruit ripening (Tieman et al, 2001;Chen et al, 2004), and participate in the response to stresses involving salt (Cao et al, 2007;Zhang et al, 2011), cold (Shi et al, 2012), iron deficiency (Bauer and Blondet, 2011), and sulfur deficiency (Maruyama-Nakashita et al, 2006). In addition, EIN3/EIL proteins participate in the cross-talk between ethylene signaling and other signaling, including those of gibberellins , salicylic acid (Chen et al, 2009) jasmonic acid (Zhu et al, 2011), and glucose (Yanagisawa et al, 2003).…”
Section: Introductionmentioning
confidence: 99%